Improving Voltage Disturbance Rejection for Variable-Speed Wind Turbines - Saccomando, G.; Svensson, J.; Sannino, A. (IEEE power engineering review, 2002)
In this paper, the effect of voltage dips on variable-speed wind turbines using VSCs is treated. Three different current controllers for the VSC are described and implemented. Their performance is evaluated when the converter is subject to different types of voltage dips. Both simulated and measured dips are used. The effect of the phase-angle jump of the dips is also taken into account.